BLOCKCHAIN ADOPTION IN PROJECT MANAGEMENT: EXPLORING ORGANIZATIONAL AND LEGAL CHALLENGES THROUGH SLR AND TOPSIS - Mohamed Al Ali; Mohammad Khadem (Operational Research in Engineering Sciences: Theory and Applications, 2025)
Blockchain technology is widely recognized as a form of distributed ledger technology, which holds substantial promise for driving economic and social transformation. However, despite growing global interest its adoption within organizational project management practices remains limited. This study seeks to investigate the underlying factors contributing to this slow uptake by employing a mixed-method approach. The research integrates a systematic literature review (SLR) of 19 peer-reviewed articles published between 2019 and 2024 to identify key challenges with a particular focus on organizational change management and legal compliance, through thematic synthesis the study uncovers critical technological and institutional barriers that hinder adoption. To prioritize and evaluate the most influential challenges the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) was applied using the web-based tool OnlineOutput enabling an efficient and structured multi-criteria decision-making framework. Results underscore the importance of leadership and strategic support deficiencies in shaping blockchain integration outcomes. The study contributes both a theoretical and practical lens for understanding blockchain adoption in project management and identifies key research gaps to inform future investigation.